Nanoparticle technology handbook - Hosokawa, Masuo (Amsterdam ; London : Elsevier Science, 2007)
Nanoparticle technology, which handles the preparation, processing, application and characterisation of nanoparticles, is a new and revolutionary technology. It becomes the core of nanotechnology as an extension of the conventional Fine Particle / Powder Technology. Nanoparticle technology plays an important role in the implementation of nanotechnology in many engineering and industrial fields including electronic devices, advanced ceramics, new batteries, engineered catalysts, functional paint and ink, Drug Delivery System, biotechnology, etc.; and
makes use of the unique properties of the nanoparticles which are completely different from those of the bulk materials. This new handbook is the first to explain complete aspects of nanoparticles with many application examples showing their advantages and advanced development. There are handbooks which briefly mention the nanosized particles or their related applications, but no handbook describing the complete aspects of nanoparticles has been published so far. The handbook elucidates of the basic properties of nanoparticles and various nanostructural materials with their characterisation methods in the first part. It also introduces more than 40 examples of practical and potential uses of nanoparticles in the later part dealing with applications. It is intended to give readers a clear picture of nanoparticles as well as new ideas or hints on their applications to create new materials or to improve the performance of the advanced functional materials developed with the nanoparticles.
Nano particle formation of DNA (globule transformation) -- Addressing of nano-particles by using DNA molecules -- Development of high performance electrochemical reactors Chapter -- Dendrimers and their application -- Electrical conductive CNT dispersed Si3N4 ceramics -- Development of functional skincare cosmetics using biodegradable PLGA nanospheres -- Development of photonic crystals based on nanoparticle assembly -- Liquid-crystalline inorganic nano- and fine- particles -- Closely packed colloidal crystal assembled with nano-particles and its application for smart materials with tunable structural color Chapter -- Development of new cosmetics based on nanoparticles -- Dispersion control of AL203 nano-particles in ethanol Chapter -- Development of thermoresponsive magnetic nanoparticle and its deployment in the biotechnology field -- Development of fuel cells -- Delivery to the brain -- Nozzle-free ink jet technology -- Development of exhaust catalyst -- Development of optical memory using semiconductor nanoparticles -- Development of bright phosphors using glasses incorporating semiconductor nanoparticles -- Development of photocatalyst inserted into surface of porous aluminosilicate -- AC overhead transmission line audible noise reduction measures using surface improvement -- Development of a high performance secondary battery by controlling the surface structure Chapter -- Pinpointed delivery Chapter 38. Expression of optical function by nanostructure using femtosecond laser processing -- Instantaneous nano-foaming method for fabrication of closed-porosity silica particle -- Evaluation and applications of dispersing carbon nanotube CNT in the polymers -- Surface modification of inorganic nanoparticles by organic functional groups Chapter -- Fabrication technique of organic nanocrystals and their optical properties and materialization -- Bio-imaging with quantum dots -- Application of quantum dots for the bio-medical engineering
Includes index.
1
Keywords: Nanoparticles; Nanotechnology